2023
DOI: 10.3847/2041-8213/acb2b8
|View full text |Cite
|
Sign up to set email alerts
|

GOALS-JWST: Pulling Back the Curtain on the AGN and Star Formation in VV 114

Abstract: We present results from the James Webb Space Telescope Director’s Discretionary Time Early Release Science program 1328 targeting the nearby, luminous infrared galaxy, VV 114. We use the MIRI and NIRSpec instruments to obtain integral-field spectroscopy of the heavily obscured eastern nucleus (V114E) and surrounding regions. The spatially resolved, high-resolution spectra reveal the physical conditions in the gas and dust over a projected area of 2–3 kpc that includes the two brightest IR sources, the NE and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…The Q-branches of C 2 H 2 , HCN, and CO 2 , blends of closely spaced pure vibrational lines, have been detected by Spitzer toward a handful of local U/LIRGs (Lahuis et al 2007), but at lower spatial and spectral resolution. Rich et al (2023) previously reported the detection of the ν 2 14.0 μm band of HCN and the ν 5 13.7 μm band of C 2 H 2 in absorption toward the NE core in VV 114E. The fundamental band of CO at 4.67 μm, tracing transitions between the ground state and the first vibrationally excited state, has been observed in absorption toward several heavily obscured U/LIRGs from the ground (e.g., Spoon et al 2003;Geballe et al 2006;Shirahata et al 2013;Baba et al 2022;Ohyama et al 2023).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The Q-branches of C 2 H 2 , HCN, and CO 2 , blends of closely spaced pure vibrational lines, have been detected by Spitzer toward a handful of local U/LIRGs (Lahuis et al 2007), but at lower spatial and spectral resolution. Rich et al (2023) previously reported the detection of the ν 2 14.0 μm band of HCN and the ν 5 13.7 μm band of C 2 H 2 in absorption toward the NE core in VV 114E. The fundamental band of CO at 4.67 μm, tracing transitions between the ground state and the first vibrationally excited state, has been observed in absorption toward several heavily obscured U/LIRGs from the ground (e.g., Spoon et al 2003;Geballe et al 2006;Shirahata et al 2013;Baba et al 2022;Ohyama et al 2023).…”
Section: Introductionmentioning
confidence: 95%
“…We reduced the data using JWST Science Calibration Pipeline version 1.11.1.dev1+g9975346 and calibration reference data system (CRDS) reference file jwst_1097.pmap. This is an updated version of the pipeline with respect to the one applied by Rich et al (2023).…”
Section: Nirspec Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of deep X-ray and mid-IR spectroscopy would be crucial to reveal the fraction and structure of buried AGNs in U/LIRGs, which are the key population in the study of SMBH growth in obscured AGNs at z ∼ 1 and beyond (see Section 1). The James Webb Space Telescope (JWST), endowed with a supreme mid-IR spectroscopic capability and unprecedentedly high sensitivity, can identify rapidly growing SMBHs in U/LIRGs (e.g., Inami et al 2022;Rich et al 2023). JWST observations combined with high-quality X-ray observations would enable us to identify buried AGNs almost fully covered by dense circumnuclear material with high ( ) f CT spec at cosmic noon, the population of which is predicted to increase significantly toward higher redshifts (e.g., Ueda et al 2014;Gilli et al 2022), and would help us reveal the entire picture of growth of both obscured and unobscured SMBHs.…”
Section: Future Observations With X-ray and Ir Spectroscopymentioning
confidence: 99%
“…Spatial variations in PAH emission have even been resolved in a lensed galaxy at z = 4.2 (Spilker et al 2023). The high spectral resolution has also enabled kinematic studies of shocks and outflows (e.g., Vivian et al 2022;Goold et al 2023;Rich et al 2023). Lines such as [Ar II]6.99 μm are strong in nearby infrared-luminous galaxies (e.g., Vivian et al 2022), and have yet to be explored beyond the local Universe.…”
Section: Introductionmentioning
confidence: 99%